Efek Mediasi Persepsi Kegunaan terhadap Pengaruh Daya Tarik terhadap Dorongan Belanja Impulsif: - Welan Mauli Angguna; Astika Ulfah Izzati; Frianka Anindea; Claudya Nurcahaya; Andriansyah; Shally Rizkiyanti; Ardelia Suharmanto (Universitas Muhammadiyah Palembang, 2025)
Purpose – The purpose of this study is to understand how attractiveness (affective reaction) influenced urge to buy impulsively through the mediation of perceived Usefulness (cognitive reaction). The research hypothesis is that there is an indirect effect between attractiveness and urge to buy impulsively through mediation of perceived usefulness. Design/methodology – This study used a one-time non-experimental quantitative research design that was tested on 165 respondents who had shopped in live streaming commerce. The survey was carried out online through non-randomized convenience sampling techniques. A measuring tool used in the form of a questionnaire that asks for an assessment of several statements. The statistical analysis was used to test mediation effect by using mediation PROCESS MACRO for SPSS by Hayes (Model 4). Findings – The results of the analysis showed that usability acceptance had a mediating effect on the effect of attraction on impulsive shopping impulses in consumers who had shopped on live streaming commerce. The immediate effect became insignificant when controlled with the mediation variable. The next study is suggested to be tested on different groups of respondents to test universality, test more specifically by differentiating e-commerce and so-commerce with more comprehensive variables and then can be tested with experimental methods to improve the internal validity of the study results.